Cultivation of Helianthus annuus L. cv. Sunflower Sunspot Dwarf with silicon application - Uhdre, R. S.; Manningel, A. R.; Ecker, A. E. A.; Sorace, M.; Castaldo, J. H.; Nolla, A. (Scientific Electronic Archives, 2017)
In recent years Brazil has been presenting a constant production of flowers and ornamental plants, with an increase in diversity, quantity and quality. As for the Sunflower ornamental dwarf, in addition to the production of vegetable oil, may be an alternative in floriculture. The objective of the present work was to verify the effect of the use of silicon doses in the production and development of chapters of the ornamental dwarf sunflower crop cultivated in a pot under protected environment. The experiment was conducted from seeds of the hybrid Helianthus annuus L. cv. Sunflower Sunspot Dwarf. The substrate used in the vessels was based on pinus bark with vermiculite, perlite and rooting. The seeds were seeded in trays of expanded polystyrene, and after germination were transplanted in polypropylene pots with 10 replicates, totaling 50 plants. The irrigation system used was the micro sprinkler and the recommended fertilization for the crop weekly. The application of silicon was performed weekly at doses 0,0 g L-1 (Witness); 0.5 g L-1; 1.0 g L-1; 1.5 g L-1 and 2.0 g L-1. The evaluations of the agronomic parameters were: plant height, stem and inflorescence diameters. For the plant height variable, the control group had the highest growth. For stem diameter and inflorescence there was no significant difference between treatments. The weekly application frequency and the silicon doses did not result in significant differences in stem diameter and inflorescence parameters evaluated for the ornamental plant Helianthus annuus L. cv. Sunflower Sunspot Dwarf compared to the witness.